Writing Research and Specialized Communication Studies - Heidrich, Franziska; Schubert, Klaus (HERMES - Journal of Language and Communication in Business, 2019)
Many research strands have a focal interest in writing as an object. Still, many representatives of these strands are not aware of the others’ existence, let alone their common ground. This paper shall serve to unveil some of the overlaps between two of the afore-mentioned research strands–or rather disciplines: Writing Research and Specialized Communication Studies. The authors outline some of the most prominent aspects concerning the evolution, the paradigms, the principles of modelling and main research lines of the disciplines, respectively, and compare them with each other. While Writing Research has been an acknowledged discipline for decades, this does not apply for Specialized Communication Studies: with its roots in LSP Studies and Translation Studies, from which it has evolved slowly but steadily, it has meanwhile become an own sphere of research, situated within the wider scope of Applied Linguistics. Today, one can claim that there is indeed the need for one independent discipline dealing with specialized communication in all its manifestations. On the basis of the afore-mentioned contrasting juxtaposition, the authors discuss what the common ground of Writing Research and Specialized Communication Studies is, where the disciplines differ, which approaches–if so–combine the two disciplines and how they may benefit from each other.